Динамика жирового обмена у куколок тутового, дубового и непарного шелкопрядов в различных экологических условиях - Синицкий, Н.Н.; Киреева, И.М. (Вестник зоологии, 1968)
The authors studied the effect of light and temperature in various combinations on dynamics of fat metabolism in pupae of insects with different biology and belonging to various families: Bombicidae, Liparidae and Saturnidae. The effect of a light factor on the development of pupae of Bombyx mori L., Anthe-raea pernyi G. M. and Porthetria dispar L. was studied in the following variants: twenty-four-hour illumination, illumination during 17, 12, 7 hours and twenty-four-hour dark-ness. In each variant the investigation of the effect of the photothermal conditions on pupa development was carried out at temperatures of 16, 18, 22, 25, 28 and 32°. As a result of the investigations it is established that in the investigated species of Lepidoptera a community is found in proceeding some physiological processes at the pupa stage. The pupae of the investigated species differ in the quantitative fat content while the type of changing fat metabolism completely coincides. During the initial and terminal periods of pupa development a considerable amount of fat is spent, at intermediate period the fat expenditure remains low. The highest fat expenditure is observed at the second part of metamorphosis. Photothermal conditions affect the dynamics of fat me-tabolism in pupae. At low temperatures with a prolongation of illumination period the metamorphosis duration is reduced and intensity of fat metabolism dynamics is somewhat increased. Under conditions of elevated temperature the minimal expenditure of general fat amount is observed under condition of 12-17 — hour illumination. On the basis of the experimentary data on fat metabolism dynamics depending on photothermal conditions, it is established that the pupa of the last days of development are mostly sensitive to the temperature and light and during the intermediate period of metamorphosis they are mostly resistant to those factors.